Antimicrobial Resistance in Enterococcus spp. of animal origin - Torres, Carmen; Alonso, Carla Andrea; Ruiz-Ripa, Laura; León-Sampedro, Ricardo; Del Campo, Rosa; Coque, Teresa M. (Microbiology spectrum, 2018)
Enterococci are natural inhabitants of the intestinal tract in humans and many animals, including food-producing and companion animals. They can easily contaminate the food and the environment, entering the food chain. Moreover, Enterococcus is an important opportunistic pathogen, especially the species E. faecalis and E. faecium , causing a wide variety of infections. This microorganism not only contains intrinsic resistance mechanisms to several antimicrobial agents, but also has the capacity to acquire new mechanisms of antimicrobial resistance. In this review we analyze the diversity of enterococcal species and their distribution in the intestinal tract of animals. Moreover, resistance mechanisms for different classes of antimicrobials of clinical relevance are reviewed, as well as the epidemiology of multidrug-resistant enterococci of animal origin, with special attention given to beta-lactams, glycopeptides, and linezolid. The emergence of new antimicrobial resistance genes in enterococci of animal origin, such as optrA and cfr , is highlighted. The molecular epidemiology and the population structure of E. faecalis and E. faecium isolates in farm and companion animals is presented. Moreover, the types of plasmids that carry the antimicrobial resistance genes in enterococci of animal origin are reviewed.